Study on the cyclic leaching performance of lead sulfate from waste lead paste by triethylene tetramine - CHEN Biao; HUANG Ming; CAO Jing; ZHANG Junfeng* (能源环境保护)
The recycling of waste lead paste is the focus of the lead recycling industry. Traditional fire smelting has issues with high energy consumption and heavy pollution. Wet conversion is a green and low-carbon recycling technology for waste lead paste, but its leaching efficiency and recycling of leaching agent need further improvement. In this study, triethylenetetramine (TETA) was used as a leaching agent to investigate the cyclic leaching of PbSO_4 from waste lead paste. An effective leaching model was established using the response surface method, and the leaching reaction parameters were optimized. With a n(TETA/PbSO_4) ratio of 1.3, a reaction time of 11 minutes, a liquid-solid ratio of 2, and a reaction temperature of 30 ℃, the predicted leaching rate of PbSO_4 was 99.99%, achieving an actual leaching rate of 99.93%. The apparent activation energy of PbSO_4 leaching reaction was found to be 47.5 kJ/mol. Furthermore, high-purity PbCO_3 with an impurity content of 0.020 4% could be obtained from TETA-Pb solution by using Na_2CO_3. This process allows for the regeneration cycle of TETA while maintaining a leaching rate of PbSO_4 above 90% in 10 cycles. The results provide a reference for the high-value utilization of waste lead paste.